The changes in melanocyte number and melanin density occurring in vitiligo patches during 180 days of narrow band-ultraviolet B therapy. Issue 1 (January 2015) - Anbar, Tag S.; Moftah, Noha H.; El-Khayyat, Mohamed A. M.; Abdel-Rahman, Amal T.; Abdel-Raouf, Hamza
<x xml:space="preserve">Abstract</x> Background Narrow band-ultraviolet B (NB-UVB) has been used in the treatment of vitiligo for years, but the sequence of events of repigmentation, occurring throughout the period of NB-UVB treatment for restoring melanocytes and melanin density, is not clear. Objective This study aimed to follow up the changes in melanocyte number and melanin density in vitiliginous patches during NB-UVB therapy for vitiligo patients. Patients and methods This study included 25 patients with nonsegmental vitiligo. NB-UVB therapy was given twice weekly for 6 months. Four skin biopsies were obtained from each patient at days 0, 30, 90, and 180. Biopsies were stained using hematoxylin and eosin stain, Masson–Fontana stain, and human melanoma black-45 (HMB-45) antibody. Qualitative and quantitative measurements were determined for both melanocyte number and melanin density. Results There was a significant increase in the number of HMB-45-negative melanocytes (P<0.000) at day 30 of therapy compared with day 0. At day 90, there was a significant increase in the number of HMB-45-positive melanocytes (P<0.001) and melanin (P<0.001) compared with days 0 and 30. As regards HMB-45-negative cells at day 90, there was a significant increase in its number compared with day 0 (P<0.001) with no significant increase compared with day 30 (P=0.13). At day 180, there was a significant increase in the number of HMB-45-positive melanocytes (P<0.001) and melanin (P<0.001) but with a significant decrease in HMB-45-negative melanocytes (P<0.001) compared with days 30 and 90. Conclusion We concluded that the sequence of events of repigmentation started with the appearance of inactive melanocytes, which were first detected at day 30, followed by the appearance of active melanocytes, melanin, and clinical repigmentation at day 90, which reached its highest levels at day 180. Moreover, we concluded that the presence of inactive melanocytes at day 30 might represent an index of favorable prognosis.